Nerve Conduction Studies in Patients with Lumbosacral Radiculopathy Caused by Lumbar Intervertebral Disc Herniation - Safa Yousif; Ammar Ahmed; Ahmed Abdelhai; Afraa Musa (Advances in Orthopedics)
Background. Nerve conduction studies (NCS) are electrodiagnostic tests used to evaluate peripheral nerves functions and aid in the assessment of patients with neuromuscular complaints. There is contrasting evidence concerning the use of NCS in the assessment of patients with lumbosacral radiculopathy. Objectives. This study was conducted to evaluate nerve conduction studies abnormalities in patients with lumbosacral radiculopathy and to find out their relation to abnormal physical examination findings. Materials and Methods. Twenty-seven patients with lumbosacral radiculopathy caused by L4/5 or L5/S1 intervertebral disc prolapse confirmed by magnetic resonance imaging (MRI) were recruited in the study. Twenty-five healthy subjects matched in age and sex served as control. Motor nerve conduction study bilaterally for both common peroneal and tibial nerves, F-wave for both nerves, and H-reflex had been conducted. Results. No significant difference was found in the motor nerve conduction study parameters (latency, amplitude, and conduction velocity) between the patients group and the control group. There was significant prolongation in H-reflex latency of both symptomatic and asymptomatic side in the patients group compared to the control group (P<0.05). Also, F-wave latencies (F minimum, F maximum, and F mean) of the tibial nerve were significantly prolonged (P<0.05) compared to control. Conclusion. Prolonged H-reflex latency was the commonest encountered abnormality in our study followed by F-wave latencies of the tibial nerve.